Development of Facile and Versatile Platinum Drug Delivering Silicasome Nanocarriers for Efficient Pancreatic Cancer Chemo‐Immunotherapy. Issue 14 (7th March 2021) - Liu, Xiangsheng; Jiang, Jinhong; Chang, Chong Hyun; Liao, Yu‐Pei; Lodico, Jared J.; Tang, Ivanna; Zheng, Emily; Qiu, Waveley; Lin, Matthew; Wang, Xiang; Ji, Ying; Mei, Kuo‐Ching; et al.
Abstract: In this study a mesoporous silica nanoparticle (MSNP) based platform is developed for high‐dose loading of a range of activated platinum (Pt) chemo agents that can be attached to the porous interior through the use of electrostatic and coordination chemistry under weak‐basic pH conditions. In addition to the design feature for improving drug delivery, the MSNP can also be encapsulated in a coated lipid bilayer (silicasome), to improve the colloidal stability after intravenous (IV) injection. Improved pharmacokinetics and intratumor delivery of encapsulated activated oxaliplatin (1, 2‐diamminocyclohexane platinum(II) (DACHPt)) over free drug in an orthotopic Kras‐derived pancreatic cancer (PDAC) model is demonstrated. Not only does IV injection of the DACHPt silicasome provide more efficacious cytotoxic tumor cell killing, but can also demonstrate that chemotherapy‐induced cell death is accompanied by the features of immunogenic cell death (ICD) as well as a dramatic reduction in bone marrow toxicity. The added ICD features are reflected by calreticulin and high‐mobility group box 1 expression, along with increased CD8 + /FoxP3 + T‐cell ratios and evidence of perforin and granzyme B release at the tumor site. Subsequent performance of a survival experiment, demonstrates that the DACHPt silicasome generates a significant improvement in survival outcome, which can be extended by delayed administration of the anti‐PD‐1 antibody. Abstract : Stable and highly efficient loading of activated platinum drugs is achieved using a silicasome nanocarrier through the use of electrostatic and coordination chemistry. This enables chemo‐immunotherapy illustrated by an activated oxaliplatin (1, 2‐diamminocyclohexane platinum(II), DACHPt) laden silicasome, which provides a strong immunogenic cell death stimulus at Kras‐mutated pancreatic cancer site. DACHPt laden silicasome synergizes with anti‐PD‐1 yielding superior anti‐cancer effect in vivo.